1989
DOI: 10.1159/000125220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Histamine Depletion on Circadian Variations of Corticotropin and Corticosterone in Rats

Abstract: The effects of cerebral histamine depletion induced by α-fluoromethylhistidine (FMH) on corticotropin (ACTH) and corticosterone secretions were examined. Neither acute nor chronic FMH treatment altered the corticoadrenal responses to three types of stress: transposition, immobilization and water immersion. And exposure to stress did not affect the hypothalamic content of histamine. However, chronic intracerebral treatment with FMH had a significant effect on the circadian rhythm of the plasma corticosterone (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…We found that a-FM H, which is a specific inhibitor o f neu ronal HA synthesis [14,15], reduced the stress-induced release o f ACTH and a-M SH in male rats but had no effect on the basal secretion o f the two hormones. It has earlier been shown that depletion o f brain HA by a-FM H decreased the basal plasma corticosterone level in young and old male rats [19], and that a-FM H had a significant effect on the circadian rhythm o f ACTH and corticosterone secretion in female rats [20]. However, it has also been reported that a-FM H did not inlluence the stress-stimulated plasma corticosterone level in female rats [20] or plasma ACTH bioactivity in male rats [21].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We found that a-FM H, which is a specific inhibitor o f neu ronal HA synthesis [14,15], reduced the stress-induced release o f ACTH and a-M SH in male rats but had no effect on the basal secretion o f the two hormones. It has earlier been shown that depletion o f brain HA by a-FM H decreased the basal plasma corticosterone level in young and old male rats [19], and that a-FM H had a significant effect on the circadian rhythm o f ACTH and corticosterone secretion in female rats [20]. However, it has also been reported that a-FM H did not inlluence the stress-stimulated plasma corticosterone level in female rats [20] or plasma ACTH bioactivity in male rats [21].…”
Section: Discussionmentioning
confidence: 89%
“…It has earlier been shown that depletion o f brain HA by a-FM H decreased the basal plasma corticosterone level in young and old male rats [19], and that a-FM H had a significant effect on the circadian rhythm o f ACTH and corticosterone secretion in female rats [20]. However, it has also been reported that a-FM H did not inlluence the stress-stimulated plasma corticosterone level in female rats [20] or plasma ACTH bioactivity in male rats [21]. The discrepancies between these studies are difficult to explain since almost the same time schedule and the same doses of a-FM H were used.…”
Section: Discussionmentioning
confidence: 89%
“…Inhibition of HA synthesis disrupts the circadian rhythms of locomotor activity, sleep, and corticosterone release (Itowi et al. , , ) and histamine‐1 receptor knockout (KO) mice exhibit disruption of the circadian rhythms with decreased activity during the active phase (Inoue et al. ; Barbier and Bradbury ).…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that HA can phase-shift the circadian neural activity rhythms in rodent SCN slices (Cote and Harrington 1993;Meyer et al 1998;Biello 2009;Kim et al 2015). Inhibition of HA synthesis disrupts the circadian rhythms of locomotor activity, sleep, and corticosterone release (Itowi et al 1989(Itowi et al , 1990(Itowi et al , 1991 and histamine-1 receptor knockout (KO) mice exhibit disruption of the circadian rhythms with decreased activity during the active phase (Inoue et al 1996;Barbier and Bradbury 2007). More recent work has found that the H3R KO exhibits substantially reduced locomotor activity rhythms (Rozov et al 2015) without a change in the peak/trough expression of core clock genes (Gondard et al 2013;Rozov et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The central circadian pacemaker is the hypothalamic suprachiasmatic nucleus (SCN). In rodents, chronic depletion of histamine results in an abolishment of the circadian rhythmicity of cortisol (Itowi et al, 1989). The influence of histamine on circadian rhythms is further illustrated by the observation that the TMN and SCN are reciprocally connected.…”
Section: Tuberomamillary Nucleusmentioning
confidence: 98%